MONITORING OF DRUG SAFETY IN CLINICAL PRACTICE - N. V. Verlan; E. O. Kochkina; N. N. Soboleva; O. A. Solodukhina (Acta Biomedica Scientifica)
The results of work on identification and registration of complications of medicinal therapy in medical institutions of the Irkutsk region showed that that the frequency of undesirable medicinal reactions in patients made from 10 to 30 %. The standard scheme of antibacterial therapy results in resistance of pathogenetic flora. Hospital patients have great possibility of being infected with microorganisms, the so-called hospital strains (bacteria). The drug safety monitoring showed the necessity of the policing of prescribing of cardiovascular, antibacterial and antiglaucoma drugs.